A comparison of pretreatments on release of sugars from sweet sorghum bagasse for bioethanol production. Issue 6 (3rd May 2017) - Banerji, Aditi; Kishore, V. V. N.; Balakrishnan, Malini
ABSTRACT: Dilute acid pretreatment and steam pretreatment were evaluated for maximum sugars release and ethanol production from sweet sorghum bagasse (SSB). The fermentation potential of the condensate and hydrolysate obtained from steam pretreatment (10 kg/cm 2, 10 minutes) and dilute acid hydrolysis (1% (w/w) sulphuric acid, 25% substrate loading) respectively, was checked with Pichia stipitis NCIM 3497 and Debaryomyces hansenii sp. Ethanol production and yield using acid hydrolysate was higher with Debaryomyces hansenii sp. (28.4 g/L and 0.37 g/g respectively) as compared with Pichia stipitis NCIM 3497 (21.9 g/L and 0.29 g/g respectively).